Implementation of Religious Moderation Values in Early Childhood - Irsyad, Mohammad (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
This research aims to determine the implementation of religious moderation values that take place in the learning process in early childhood. Type of field research with a qualitative approach. Data analysis techniques are data reduction (data reduction), data display (data presentation) and conclusion drawing/verification (drawing conclusions). The research results show that implementing the values of religious moderation is found in several learning themes, namely the theme of my environment, the theme of my country, and the theme of my work. In the learning process, the greetings take the form of versions of two religions; pray before and after carrying out activities; sticking pictures of places of worship, and singing national songs, introducing national symbols, holidays, and pictures of heroes; prayer before and after eating according to two religions; introduction to places of worship, traditional houses, and traditional figures.